Performance evaluation of locally developed black light trap for maize insects monitoring in Chitwan, Nepal - Bhandari, Ghanashyam; Jha, Shiva Kumar; Giri, Yagya Prasad; Manandhar, Hira Kaji; Jha, Pramod Kumar; Devkota, Nabaraj; Thapa, Praseed; Thapa, Resham Bahadur (Journal of Maize Research and Development, 2018)
Till today, the light traps in Nepal are found using with traditional type, which have not being recognized internationally. These light traps were of low efficiency for trapping insects as compared to black light trap (BLT). The black light tube (F10T8/BL) was used in newly constructed trap at National Maize Research Program (NMRP), Rampur, Chitwan, Nepal. Both traps were installed at the maize experimental field at NMRP during February to October, 2017. Data on insect numbers were recorded once in a week from dusk to down in two different days to minimize the light effects of each others. The total number of insects trapped in BLT was 2804 as compared to 868 in traditional light trap (TLT). Among the insect orders, Coleopterans were mostly trapped in BLT followed by Lepidopteron and Hemipterans. The results showed that the trapping efficiency of BLT was three fold higher than that of TLT. Therefore, black light trap was highly effective monitoring tool and its field applications are expected to be commercialized.